A Preliminary Calculation of Three-Dimensional Unsteady Underwater Cavitating Flows Near Incompressible Limit (Communications in Computational Physics, 2008)
Recently, cavitated flows over underwater submerged bodies have attractedresearchers to simulate large scale cavitation. Comparatively Computational FluidDynamics (CFD) approaches have been used widely and successfully to model developed cavitation. However, it is still a great challenge to accurately predict cavitatedflow phenomena associated with interface capturing, viscous effects, unsteadiness andthree-dimensionality. In this study, we consider the preconditioned three-dimensionalmultiphase Navier-Stokes equations comprised of the mixture density, mixture momentum and constituent volume fraction equations. A dual-time implicit formulationwith LU Decomposition is employed to accommodate the inherently unsteady physics.Also, we adopt the Roe flux splitting method to deal with flux discretization in space.Moreover, time-derivative preconditioning is used to ensure well-conditioned eigenvalues of the high density ratio two-phase flow system to achieve computational efficiency. Validation cases include an unsteady 3-D cylindrical headform cavitated flowand an 2-D convergent-divergent nozzle channel cavity-problem.